The constitution of war in the Middle East - Samad Zangana; Oudha Yousif; Anas Akram Mohammed Subhi Abbas; Aqeel Nadea Abdulateef (Encuentros)
The intricate military operations in the Middle East are impacted by the constitutional frameworks in the area, resulting in significant global ramifications. The article explores the constitutional basis that grants legal authority for military operations in the region.  This study aims to examine the constitutional systems that provide authorization for war in the Middle East, assessing their impact on regional and global peace, security, accountability, and the safeguarding of human rights. This study assesses the influence of these frameworks on both the stability of the area and the broader international community, with a particular focus on the significance of transparency and responsibility in managing conflicts. The results suggest that attaining peace and stability in the Middle East is intricately linked to a thorough understanding of its constitutional systems that foster conflict. This study underscores the urgent need for more transparency and responsibility in the legal and political processes that culminate in armed conflict, underscoring their importance in upholding peace and security.